2014
DOI: 10.1074/jbc.m113.536920
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Mitochondrial Clearance Predispose Human Monocytes to Interleukin-1β Hypersecretion

Abstract: Background: Periodic fever syndromes are caused by deregulation of interleukin-1␤ release. Results: Defective autophagy leads to accumulation of damaged mitochondria in monocytes. Conclusion: Mitochondrial components in the cytosol cause priming of monocytes for interleukin-1␤ release. Significance: The molecular mechanism behind deregulated cytokine secretion provides new clues for intervention.Most hereditary periodic fever syndromes are mediated by deregulated IL-1␤ secretion. The generation of mature IL-1␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 46 publications
(77 reference statements)
2
81
0
Order By: Relevance
“…129 Recent studies have identified a key role of autophagy in activation of the NLRP3 inflammasome. [130][131][132][133] Autophagy acts as a negative regulator of NLRP3 inflammasome activation through various mechanisms, including direct inhibition of NLRP3 inflammasome activation by removing sources of endogenous NLRP3 inflammasome agonists, such as damaged mitochondria and mitochondrial DNA, 62,69,132 suppression of IL-1b secretion by targeting pro-IL-1b for lysosomal degradation, 134 and selective degradation of inflammasome components, such as NLRP3 and ASC. 131,135 More detailed information on the negative regulation of the NLRP3 inflammasome, including the roles of microRNAs and autophagy, has been detailed in recent reviews.…”
Section: Negative Regulation Of Nlrp3 Inflammasome Complex Activationmentioning
confidence: 99%
“…129 Recent studies have identified a key role of autophagy in activation of the NLRP3 inflammasome. [130][131][132][133] Autophagy acts as a negative regulator of NLRP3 inflammasome activation through various mechanisms, including direct inhibition of NLRP3 inflammasome activation by removing sources of endogenous NLRP3 inflammasome agonists, such as damaged mitochondria and mitochondrial DNA, 62,69,132 suppression of IL-1b secretion by targeting pro-IL-1b for lysosomal degradation, 134 and selective degradation of inflammasome components, such as NLRP3 and ASC. 131,135 More detailed information on the negative regulation of the NLRP3 inflammasome, including the roles of microRNAs and autophagy, has been detailed in recent reviews.…”
Section: Negative Regulation Of Nlrp3 Inflammasome Complex Activationmentioning
confidence: 99%
“…Rac1 and RhoA can be reciprocally regulated (22,23), suggesting the possibility that deficiency in RhoA prenylation may cause Rac1 activation and thereby drive IL-1␤-driven autoinflammation. We tested this hypothesis in a culture-based MKD model, where THP-1 monocytic cells were pretreated 24 to 48 h with 10 M simvastatin (13,15). Simvastatin targets HMG-CoA reductase, the rate-limiting enzyme in the cholesterol synthesis cascade.…”
Section: Prenylation-deficient Rhoa Has Reduced Gtp Binding Activity mentioning
confidence: 99%
“…Inhibition of Rac1 in THP-1 monocyte cultures leads to normalization of IL-1␤ levels (14). Yet there are a number of other biochemical hallmarks of MKD, including altered autophagy, mitochondrial potential, and morphology and redox balance that cannot be explained by aberrant activity of Rac1 alone (15). Henneman et al (16) reported that RhoA, normally prenylated, activity was increased in MKD patient-derived fibroblasts, which however do not display the autoinflammation phenotype.…”
mentioning
confidence: 99%
“…MKD patients exhibit periodic fever syndrome and hypersecretion of IL-1 and IgD. Interestingly, improved efficiency of mevalonate kinase folding in MKD does not attenuate clinical symptoms, suggesting that protein misfolding/ stablility may be altered, potentially priming the NLRP3 inflammasome by inducing expression of pro-IL-1 [31]. The ER stress in MKD has been linked to defective mitophagy and neutralization of mtROS in MKD reduces inflammasome activity.…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%
“…Interestingly, MKD cells were resistant to reduction in IL-1 production by the autophagy activator rapamycin, suggesting that the isoprenoid MKD defect may activate the inflammasome through a mechanisms not regulated by autophagy [31]. Genetic defects in the proteasome itself have been recently found to cause autoinflammatory disease.…”
Section: Autoinflamamatory Diseases Linked To Disorders In Protein MImentioning
confidence: 99%